Persistent Herpes Simplex Virus Type 1 Infection of Enteric Neurons Triggers CD8+ T Cell Response and Gastrointestinal Neuromuscular Dysfunction - Brun, Paola; Conti, Jessica; Zatta, Veronica; Russo, Venera; Scarpa, Melania; Kotsafti, Andromachi; Porzionato, Andrea; De Caro, Raffaele; Scarpa, Marco; Fassan, Matteo; Calistri, Arianna; Castagliuolo, Ignazio (Frontiers in Cellular and Infection Microbiology, 2021)
Behind the central nervous system, neurotropic viruses can reach and persist even in the enteric nervous system (ENS), that is, the neuronal network embedded in the gut wall. We recently reported that immediately following intragastric (IG) administration, Herpes simplex virus (HSV)-1 infects enteric neurons and recruits mononuclear cells in the myenteric plexus of laboratory animals. We took those findings a step forward in the current work by investigating the persistence of HSV-1 in the ENS and the specific local adaptive immune responses against HSV-1 that might contribute to neuronal damage in an animal model. While our experiments disclosed specific viral RNA transcripts and proteins in the longitudinal muscle layer containing the myenteric plexus (LMMP) up to 10 weeks post HSV-1 infection, no infectious particles were detected indicating viral abortive replication. CD3+CD8+INFγ+ lymphocytes skewed towards HSV-1 antigens nevertheless infiltrated the myenteric ganglia starting from the 6th week of infection and persisting up to 10 weeks post-IG HSV-1 inoculation. CD3+CD8+ cells isolated from the LMMP of the infected mice specifically recognized HSV-1 antigens expressed by infected enteric neurons. Infiltrating activated lymphocytes were involved, in vivo, in controlling viral replication and intestinal neuromuscular dysfunction. Indeed, depleting the CD8+ cells by administering specific monoclonal antibody we observed increased expression of viral genes but a partial reduction of intestinal dysmotility in HSV-1 infected mice. The study’s findings demonstrate that HSV-1 persistently infects enteric neurons that express viral antigens, leading them to recruit activated CD3+CD8+ lymphocytes. They also support the hypothesis that specific T-cell responses toward HSV-1 antigens persistently expressed in enteric neurons can alter the integrity of the ENS predisposing to neuromuscular dysfunction.